Spoligotyping of tuberculous mycobacteria isolated from humans and cattle - N. I. Khаmmаdov; T. Kh. Faizov; K. A. Osyanin; A. V. Khаmmаdovа; K. S. Khаertynov; E. A. Shuralev (Туберкулез и болезни лёгких)
Objective: to analyze the species and genetic families of tuberculous mycobacteria isolated from humans and cattle by spoligotyping.Subjects and methods. Biological materials collected in the cattle, livestock farmers (who underwent annual fluorographic examinations) and tuberculosis patients were studied. To identify mycobacteria, the spoligotyping method was used.Results. The article assesses the variability of sites within direct repeats (spacers), which are used in laboratory diagnostics for spoligotyping of mycobacteria and identification of tuberculosis pathogens. The frequency of combinations of different spacers in the analyzed mycobacteria in the specimens identified as Mycobacterium tuberculosis complex is compared with the spoligotyping profile of known mycobacteria thus establishing their belonging to a specific genetic family The studied isolates were tested by microscopic, bacteriological, and molecular genetic (PCR) methods. Based on the results of spoligotyping, it was found out that they belonged to genetic families of M. tuberculosis of Beijing, LAM, and Haarlem.